Analisis Penerapan Materialitas, Transparansi, dan Akuntabilitas dalam Laporan Keberlanjutan Berbasis Global Reporting Initiative PT Alamtri Mineral Indonesia Tbk 2025 - Intan Nur Lizsa; Lisa Rahmawati; Agus Triyani (AKUNTANSI 45, 2026)
This study aims to analyze the implementation of materiality, transparency, and accountability principles in the sustainability report based on the Global Reporting Initiative (GRI) of PT Alamtri Minerals Indonesia Tbk in 2025. This research employed a qualitative descriptive method using a content analysis approach on the company’s sustainability report based on GRI Standards 2021. The analysis was conducted through a disclosure checklist covering GRI 2 and GRI 3, GRI 200, GRI 300, and GRI 400 to evaluate the level of compliance with the applicable standards. The results show that the company disclosed 80 out of 117 indicators with a disclosure level of 68.38%, categorized as Partially Applied. The highest disclosure level was found in general disclosures and material topics, while the economic aspect showed the lowest disclosure level. In terms of materiality, the company has identified sustainability issues relevant to the mining sector. Transparency and accountability were also implemented through the disclosure of ESG strategies, corporate governance, and sustainability risk oversight, although several indicators were still not fully disclosed. This study contributes to evaluating the quality of sustainability reporting in the mining sector based on GRI Standards 2021.